2011
DOI: 10.1111/j.1600-0706.2011.19320.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal feeding under stoichiometric constraints: a model of compensatory feeding with functional response

Abstract: When the nutrient content of food is limited, herbivores often increase their feeding rates. Such an increase in the feeding rate is called 'compensatory feeding'. Although it has a number of implications for herbivore population and plant-forager dynamics, the compensatory feeding is not yet functionally formulated especially in relation with ecological stoichiometry. Therefore, we constructed a simple mathematical model by incorporating the optimal feeding rate into the type II functional response to maximiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 46 publications
(84 reference statements)
1
51
0
Order By: Relevance
“…), such that the invertebrates in 4yB experimental plots might have consumed larger amounts of low‐quality litter to obtain the required amount of P (Suzuki‐Ohno et al. , Jochum et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), such that the invertebrates in 4yB experimental plots might have consumed larger amounts of low‐quality litter to obtain the required amount of P (Suzuki‐Ohno et al. , Jochum et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, invertebrates may consume greater amounts of a low‐quality resource to obtain the required amount of a limiting nutrient (Suzuki‐Ohno et al. , Jochum et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The slopes of these Daphnia species might have been even lower if they had not exhibited compensatory feeding. Although knowledge is still limited on compensatory feeding (Suzuki-Ohno et al 2012) and metabolic P loss (He and Wang 2007) of consumer animals, our study clearly showed that the TFC and growth response to food abundance were both affected by food P content through feeding performance for P acquirement and metabolic loss processes for maintenance. Gliwicz (1990) suggested that differences in TFC among species were related to body size, and there was a negative correlation between TFC and body size for Daphnia.…”
Section: Growth Response To Changes In Quantity and Elemental Composimentioning
confidence: 91%
“…1c). Ironically, although compensatory feeding functions to maximize the growth rate under low P content food (Suzuki-Ohno et al 2012), it may make the consumer species inferior when there is a competitor.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Variable phytoplankton elemental composition is often presumed to propagate across trophic levels in the food chain (Mitra and Flynn, 2007;Malzahn et al, 2010;Iwabuchi and Urabe, 2012b;Meunier et al, 2012a). Stoichiometric plasticity in (meso-) zooplankton seems to be both narrower and more complex than in phytoplankton (Sterner and Elser, 2002;Urabe et al, 2002a,b;Iwabuchi and Urabe, 2012a,b;Suzuki-Ohno et al, 2012;Hessen et al, 2013). However, most evidence is from marine zooplankton laboratory cultures and field data on stoichiometric variations in freshwater zooplankton, e.g., Daphnia phosphorus content and its variation in response to resource phosphorus-to-carbon (P:C) ratios (DeMott and Pape, 2005).…”
Section: Introductionmentioning
confidence: 99%